2011
DOI: 10.1016/j.neures.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel balanced chromosomal translocation found in subjects with schizophrenia and schizotypal personality disorder: Altered l-serine level associated with disruption of PSAT1 gene expression

Abstract: L-Serine is required for the synthesis of glycine and D-serine, both of which are NMDA receptor co-agonists. Although roles for D-serine and glycine have been suggested in schizophrenia, little is known about the role of the L-serine synthesizing cascade in schizophrenia or related psychiatric conditions. Here we report a patient with schizophrenia carrying a balanced chromosomal translocation with the breakpoints localized to 3q13.12 and 9q21.2. We examined this proband and her son with schizotypal personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Mutations in PSAT1 , which regulates PSPH , affect neurodevelopment (Tabatabaie et al, 2010). There is also evidence that the gene is implicated in SCZ based on a study of gene expression in a family with a chromosomal translocation near PSAT1 associated with SCZ and schizotypal personality disorder (Ozekia et al, 2012). The second gene in the interaction, SHMT2 , demonstrated the overexpression and regulatory function (suppression and promotion) in migration and proliferation in carcinoma cells (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in PSAT1 , which regulates PSPH , affect neurodevelopment (Tabatabaie et al, 2010). There is also evidence that the gene is implicated in SCZ based on a study of gene expression in a family with a chromosomal translocation near PSAT1 associated with SCZ and schizotypal personality disorder (Ozekia et al, 2012). The second gene in the interaction, SHMT2 , demonstrated the overexpression and regulatory function (suppression and promotion) in migration and proliferation in carcinoma cells (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PSAT1 is an enzyme that participates in serine synthesis pathway and increases serine levels (19), suggesting that PSAT1 might regulate TRB3 expression via altered serine levels. Although serum serine levels remained unchanged, liver serine levels were significantly increased in Ad-PSAT1 mice and decreased in Ad-shPSAT1 mice compared with their respective control mice (Fig.…”
Section: Psat1 Regulates Trb3 Expression Via Altered Serine Levels Inmentioning
confidence: 99%
“…Three steps are involved in serine synthesis (11), and PSAT1 is involved in the second step catalyzing the 3-phosphohydroxypyruvate to form L-phosphoserine (11,12). Serine contributes to the regulation of several physiological processes (13)(14)(15)(16), and, as one of a key enzymes in serine synthesis, PSAT1 has some important metabolic functions (17)(18)(19). For example, PSAT1 deficiency results in intractable seizures and acquired microcephaly (17), while increased expression of PSAT1 is associated with the development of colorectal cancer (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported that a family with schizophrenia had a chromosomal translocation, which reduced the expression of PSAT1 encoding phosphoserine aminotransferase 1, the second enzyme involved in de novo L-Ser synthesis. 6) Despite exhibiting such differing nervous symptoms as microcephaly, psychomotor retardation, and intractable seizures, patients with a genetic L-Ser deficiency have markedly decreased levels of L-and D-Ser in the cerebrospinal fluid and blood due to a mutation of PHGDH, PSAT1 or PSPH. 7) Although oral supplementation of L-and/or D-Ser is a potent therapeutic treatment for these patients, it is known that L-and D-Ser diffuse poorly through the blood-brain barrier.…”
mentioning
confidence: 99%